The impact of French as a medium of instruction on academic access and performance in Moroccan higher education - Abdessatar Azennoud; Khawla Lamghari; Achraf Guaad (Moroccan Journal of Quantitative and Qualitative Research)
This study explores students' perceptions and experiences regarding the use of French as a medium of instruction in Moroccan higher education and its impact on access to higher education. While French has historically been the dominant academic language, many students perceive it as a colonial legacy rather than a necessity for academic success. Despite extensive research on language barriers in education, limited attention has been given to their impact on students’ academic choices and access to higher education. Addressing this gap, the study employed a mixed-method research design, using a questionnaire, which is composed of both quantitative and qualitative elements, to gather data from 34 students in the English Department at Mohamed V University. The findings reveal that science students, in particular, struggle with French proficiency, significantly hindering their comprehension, participation, and overall performance. Many students reported shifting to disciplines with fewer language barriers due to their difficulties with French. Additionally, the majority rejected the necessity of French in higher education, advocating for English as a more globally relevant alternative. These findings highlight the urgent need for pedagogical and policy reforms to ensure equitable academic access. The study also serves as a trigger for policy and decision-makers to provide strong language support or transitioning toward English as an instructional language.